A Review of the Impact of the Digital Transformation on the Global and European Economy - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2021)
The paper aims to present digital transformation as a process that has been taking place in the digital economy and the European Union's economy in recent years and its impact on changes in the economic and social sphere. As a starting point, this paper considers the importance of advanced technology products in the global production and trade in the global and European economy, including information and communication technologies, which constitute the primary basis for the development of the digital economy. The paper shows that leading technologies can allow sustainable development goals (SDGs) to be achieved faster and more effectively. It is necessary to eliminate the persistent, significant income differences between developing and highly developed countries and disparities in access to the use of innovative solutions (including social innovation).
Keywords: O13; 330; transformation; digital economy; advanced technology products; global economy; European Union